Young women's engagement with gambling: A critical qualitative inquiry of risk conceptualisations and motivations to gamble. Issue 1 (24th August 2022) - McCarthy, Simone; Thomas, Samantha; Pitt, Hannah; Marko, Sarah; Randle, Melanie; Cowlishaw, Sean; Kairouz, Sylvia; Daube, Mike
Abstract: Background: Younger women's engagement with gambling has changed over recent decades due to a range of socio‐cultural, environmental and commercial factors. However, younger women's distinct lived experiences with gambling have rarely been considered. The following critical qualitative inquiry explored factors that influenced younger women's engagement with gambling and their perceptions of gambling risks. Methods: Semi‐structured interviews were conducted with 41 Australian women aged 18‐40 years. Participants were asked questions relating to their reasons for gambling, and the perceived risks associated with gambling. Reflexive thematic analysis was used to interpret the data. Results: Five themes were constructed from the data. First, women reported that they gambled to escape their everyday lives, with some women reporting gambling within their own homes. Second, women reported gambling for financial reasons, particularly to change their life circumstances and outcomes. Third, gambling was used by women as a way to connect with social network members. Fourth, gambling was an incidental activity that was an extension of non‐gambling leisure activities. Finally, lower risk perceptions of participants' own gambling risk contributed to their engagement and continuation of gambling. Conclusion: Public health and health promotion initiatives should recognise that young women's gambling practices are diverse, and address the full range of socio‐cultural, environmental and commercial factors that may influence younger women's engagement with gambling.